Development of Bekel Ball Game to Improve Cognitiveness Children aged 5-6 Years in Kec. Way Seputih Central Lampung - Tri Rahayu; Windisyah Putra (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2022)
Educational games are useful for improving language skills, cognitive skills, and getting along with the environment. Cognitive is the ability to acquire and use knowledge in order to solve problems and adapt to the environment. The researcher chose the cognitive aspect because of this ability in RA Muslimat NU 10 Sri Budaya Kec. Way Seputih, Central Lampung is still relatively undeveloped. The purpose of this research is the development of bekel ball game at RA Muslimat NU 10 Sri Budaya Kec. Way as white as Central Lampung. Types of research and development (research and development). The development procedure according to the 4D model consists of four stages, namely Define, Design, Develop, Disseminate. Based on the results of the study, it can be concluded that the development of bekel ball game media at RA Muslimat NU 10 Sri Budaya Kec. Way Seputih Central Lampung with the following steps: 1) The teacher prepares the bekel ball game media. 2) The teacher explains the rules of the game using bekel ball game media. 3) The teacher gives examples of the steps of the Bekel ball game. 4) The child is asked to roll the bekel ball. 5) The child will get a prize in the form of one star if he answers correctly, while if the child answers incorrectly, the child will get a punishment in the form of reading a short letter. 6) The child is asked to name the number symbol on the bekel ball falling hole. 7) Children are asked to count the number of numbers in each hole that the bekel ball falls. 8) Children are asked to match the number with the number symbol in each hole the bekel ball falls. 9) Each hole consists of a picture and the name of the picture. 10) The child is asked to explain each picture on the bekel ball falling hole. The Effectiveness of Using Bekel Ball Game Media to Improve Cognitive Aspects of Children aged 5-6 years at RA Muslimat NU 10 Sri Budaya Kec. Way Seputih Central Lampung which is very effective.